Lithium ion battery composite positive electrode material and preparation method thereof

By heat-treating the oxide lithium ion solid electrolyte containing a small amount of sodium ions with the positive electrode active material, forming a cladding layer and doping sodium ions, the problem of prone electrode materials of lithium ion batteries is easily broken and powdered during the circulation process, and the capacity, magnification and cycling performance of the battery are significantly improved.

CN119764383AActive Publication Date: 2025-04-04SHANGHAI INST OF SPACE POWER SOURCES
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411913982.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-04
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode materials are prone to rupture and powderization during the circulation process, resulting in a decrease in the cycle life and rate performance of the battery.

Method used

By simply physically mixing the lithium-ion solid electrolyte containing a small amount of sodium ions with the positive electrode active material and heat treatment, a cladding layer is formed and sodium ions doped inside the material, the synergistic effect of solid electrolyte coating and sodium ion doping is achieved.

Benefits of technology

This method not only provides a physical barrier with high ionic conductivity and low electronic conductivity, inhibits material cracking and powdering, but also improves the capacity, magnification and cycling performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764383A_ABST
    Figure CN119764383A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium ion battery composite positive electrode material and a preparation method thereof, the lithium ion battery composite positive electrode material comprises a positive electrode active material, the composite positive electrode material also comprises an oxide lithium ion solid electrolyte material, and the oxide lithium ion solid electrolyte material contains a small amount of sodium ions. The surface of the positive electrode active material is coated with an oxide lithium ion solid electrolyte material, and sodium ions are doped in the positive electrode active material. According to the invention, an oxide lithium ion solid electrolyte containing a small amount of sodium ions is synthesized through a lithium sodium ion exchange method, and then the oxide lithium ion solid electrolyte and a positive electrode active material are subjected to simple physical mixing and heat treatment to prepare the composite positive electrode material. The composite positive electrode material provided by the invention has synergistic benefits of two modification means of solid electrolyte coating and sodium ion doping, the capacity performance, the rate capability and the cycle performance of the positive electrode material can be remarkably improved, and the preparation process is simple and controllable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrochemistry, and in particular relates to a lithium ion battery composite positive electrode material and a preparation method thereof. Background Art

[0002] In recent decades, the rapid rise of lithium-ion (Li-ion) batteries has not only reshaped the huge portable electronic product market (such as mobile phones, smart watches, laptops, etc.), promoted the efficient use of clean energy, but also facilitated the commercialization of electric vehicles (EVs), further alleviating the growing environmental crisis caused by the high dependence on fossil fuels and carbon dioxide emissions. Therefore, lithium-ion batteries are indispensable in many applications such as portable electronics, electric vehicles, and large-scale energy storage. In lithium-ion batteries, the properties of the cathode material play a decisive role in the overall performance of the battery, especially the cathode active materials with high energy density, such as lithium nickel cobalt manganese oxide, lithium-rich manganese-based oxides, and high-voltage lithium cobalt oxide. However, these cathode active materials with high energy density are prone to rupture during the cycle process, and there are continuous side reactions between them and the electrolyte, which will seriously damage the cycle life and rate performance of the battery. Surface coating is an important strategy that can effectively improve the stability of positive electrode materials. Its specific functions include: 1) physical barrier to inhibit side reactions; 2) remove hydrofluoric acid (HF), prevent chemical corrosion of electrolytes, and reduce transition metal dissolution; 3) enhance electronic and ionic conductivity; 4) surface chemical modification to promote interfacial ion charge transfer; 5) stabilize the structure and reduce phase change stress.

[0003] Solid electrolytes have high ionic conductivity and low electronic conductivity at room temperature and are suitable as cathode coatings. Due to their high ionic conductivity, they are expected to improve charge transfer at the cathode / electrolyte interface. In addition, solid electrolyte coating provides a physical barrier and inhibits side reactions. Chinese invention patent application CN108448055A coats a continuous solid electrolyte film on the surface of the cathode material to improve the performance of the cathode material and inhibit expansion; Chinese invention patent application CN109449414A provides a core-shell structure of a solid electrolyte coated cathode material, which can improve the interface problem between the cathode and the solid electrolyte; both of the above invention patents inhibit side reactions between the cathode material and the electrolyte from the perspective of constructing a physical barrier, but cannot inhibit the cracking and pulverization of the cathode material particles themselves from a structural perspective. Chinese invention patent application CN 112310353A discloses a composite positive electrode material for lithium-ion batteries. The composite positive electrode material is obtained by filling / embedding a solid electrolyte into a bulk positive electrode material, which effectively improves the density, coulombic efficiency, rate performance and cycle life of the positive electrode material, effectively inhibits the cracking and pulverization of the material during the cycle, and can also stabilize the lattice structure of the material. However, the preparation process of this invention patent is complicated, and the introduction of the solid electrolyte needs to start from the preparation step of the positive electrode material precursor, which is not conducive to scale expansion and cost reduction. Summary of the invention

[0004] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a lithium ion battery composite positive electrode material and a preparation method thereof. The composite positive electrode material is formed by a method in which an oxide lithium ion solid electrolyte containing a small amount of sodium ions and a positive electrode active material are simply physically mixed and then heat treated. The oxide lithium ion solid electrolyte forms a coating layer on the surface of the positive electrode active material, and at the same time, a small amount of sodium ions in the oxide lithium ion solid electrolyte react with lithium ions in the positive electrode active material to form a Li+ reaction. + / Na + The exchange not only doped sodium ions in the main body of the composite cathode material particles, but also generated sodium metal oxide crystals on their surface. The composite cathode material has the synergistic benefits of two modification methods: solid electrolyte coating and sodium ion doping. It not only provides a physical barrier with high ion conductivity and low electronic conductivity for the surface of the cathode material, but also the doped sodium ions inhibit the cracking and pulverization of the cathode material during the cycle from a structural perspective, stabilizes the lattice structure, and Li + / Na + More free Li released by the exchange + It can also enable the positive electrode material to exert a higher capacity, significantly improving the capacity performance, rate performance and cycle performance of the positive electrode material.

[0005] In order to achieve the above-mentioned object, the present invention provides a lithium-ion battery composite positive electrode material, comprising a positive electrode active material, wherein the composite positive electrode material also comprises an oxide lithium ion solid electrolyte material, wherein the oxide lithium ion solid electrolyte material contains a small amount of sodium ions, and the surface of the positive electrode active material is coated with the oxide lithium ion solid electrolyte material, and sodium ions are doped inside.

[0006] The preparation method of the composite positive electrode material comprises the steps of:

[0007] S1. Accurately weigh the positive electrode active material and the oxide lithium ion solid electrolyte material in proportion;

[0008] S2, mixing the materials weighed in S1 and ball milling them to obtain a mixed material;

[0009] S3, placing the mixed material described in S2 in a tubular furnace, introducing oxygen, and calcining at 600-1000° C. for 8-12 hours to obtain the high-capacity lithium-ion battery composite positive electrode material.

[0010] The metal oxide crystals of Na generated on the surface of the composite positive electrode material are obtained by lithium-sodium ion exchange of sodium ions in the oxide lithium ion solid electrolyte material on the surface of the positive electrode active material.

[0011] The oxide lithium ion solid electrolyte material is obtained by liquid phase lithium sodium ion exchange experiment using sodium ion conductor as precursor, and the preparation method comprises the following steps:

[0012] A1. Mix the sodium ion conductor, lithium bis(trifluoromethylsulfonyl imide) and ionic liquid evenly, and put them into a reactor, wherein the concentration of lithium bis(trifluoromethylsulfonyl imide in the ionic liquid is 0.1 mol / L-0.5 mol / L, and the molar ratio of the lithium bis(trifluoromethylsulfonyl imide) to the sodium ion conductor is 3:1; put the reactor into a homogeneous reactor, rotate and stir at a speed of 50 rpm / min for 72-144 hours, and the temperature is 100-200°C;

[0013] A2. The product in the reactor is taken out and centrifuged, dried, and calcined at 400-500° C. to obtain an oxide lithium ion solid electrolyte material.

[0014] Preferably, the ionic liquid in step A1 is any one or more of imidazole ionic liquid, quaternary ammonium ionic liquid and pyrrole ionic liquid.

[0015] Preferably, the ionic liquid in step A1 comprises 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.

[0016] Preferably, the average particle size of the positive electrode active material is 5 μm≤D50≤20 μm, and the average particle size of the oxide lithium ion solid electrolyte material is 50 nm≤D50≤500 nm.

[0017] Preferably, the oxide lithium ion solid electrolyte material accounts for 0.5 wt.% to 3 wt.% of the composite positive electrode material.

[0018] Preferably, the positive electrode active material is any one of lithium cobalt oxide, olivine type, lithium nickel cobalt manganese oxide, lithium-rich manganese-based oxide, and spinel oxide.

[0019] Preferably, the oxide solid electrolyte material is Li 3-x Na x Zr2Si2PO 12 , Li 3-x Na x V2(PO4)3、Li 3- x Na x La(PO4)2、Li 3-x Na x Hf2Si2PO 12 , Li 4-y Na y Zr2(SiO4)3、Li 1-z Na z Zr2(PO4)3、Li 1.3-m Na m M 0.3 Ti 1.7 (PO4)3 or Li 1.3-m Na m Al 0.3 Ge 1.7 (PO4)3, wherein M is Al, Cr, Ga, Ge, Sc, In, Lu, Y or La, 0 <x<0.3,0<y<0.4,0<z<0.1,0<m<0.1。

[0020] The present invention also provides an application of a lithium-ion battery composite positive electrode material prepared by the method, wherein the composite positive electrode material is formed by a method in which an oxide lithium-ion solid electrolyte containing a small amount of sodium ions and a positive electrode active material are simply physically mixed and then heat-treated, wherein the oxide lithium-ion solid electrolyte forms a coating layer on the surface of the positive electrode active material, and at the same time, a small amount of sodium ions in the oxide lithium-ion solid electrolyte react with lithium ions in the positive electrode active material to form a Li+ bond. + / Na +The exchange not only doped sodium ions in the main body of the composite cathode material particles, but also generated sodium metal oxide crystals on their surface. The composite cathode material has the synergistic benefits of two modification methods: solid electrolyte coating and sodium ion doping. It not only provides a physical barrier with high ion conductivity and low electronic conductivity for the surface of the cathode material, but also the doped sodium ions inhibit the cracking and pulverization of the material during the cycle from a structural perspective, stabilize the lattice structure, and Li + / Na + More free Li is released by the exchange + It can also enable the positive electrode material to exert a higher capacity, significantly improve the capacity performance, rate performance and cycle performance of the positive electrode material, and realize a high-specific-energy and high-stability all-solid-state lithium metal battery that can operate at room temperature without any electrode modification.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] (1) The oxide lithium ion solid electrolyte used in the present invention is obtained by liquid phase lithium sodium ion exchange experiment with sodium ion conductor as precursor. Since it inherits the framework structure of the sodium ion conductor, the transmission of lithium ions therein is faster and more convenient. The obtained lithium ion solid electrolyte has high ionic conductivity. Therefore, after forming a coating layer, it can not only prevent the dissolution and corrosion of the positive electrode material, but also improve the charge transfer at the interface, reduce the resistance of the positive electrode material and increase the electrochemical reaction rate, so that the positive electrode material exhibits excellent rate performance and higher capacity retention rate.

[0023] (2) The present invention uses a heat treatment method to remove a small amount of Na in the oxide lithium ion solid electrolyte. + ions, one part of which is doped into the internal body of the composite cathode material particles, and the other part is doped into the internal body of the composite cathode material particles through Li + and Na + The exchange of Na metal oxide crystals forms on the surface of the composite cathode material particles, and various defects are formed near the surface. First, Na + Doping can effectively increase the interlayer spacing, which is beneficial to the diffusion of lithium ions between layers and improves capacity; Na + Doping can effectively inhibit Li x Ni 1-x The formation of O impurity phase increases the disorder of Ni / Mn, reduces the charge transfer impedance, accelerates the diffusion of lithium ions, and thus improves the rate performance of the material; Na + Doping plays a supporting role, preventing structural collapse and improving the stability of the material structure. Secondly, the metal oxide crystal coating of Na on the surface can prevent the electrolyte from dissolving and corroding the positive electrode material, thereby playing a protective role, and the stacking fault defects caused by it can achieve a pinning effect to maintain the layer structure. + / Na +More free Li released by the exchange + It can make the positive electrode material have a higher capacity.

[0024] (3) The present invention provides a new sodium doping modification method. + Doping can effectively improve the stability of the material structure, but controlling Na + The doping amount is crucial. Low-content sodium-doped lithium-ion cathode materials often show poor cycle stability, while high-content sodium-doped + It will also cause serious deformation and distortion of the structure of the positive electrode material, thereby reducing the capacity. Traditional sodium doping is generally added during the synthesis process of the lithium-ion positive electrode material precursor. In the subsequent synthesis steps, there is a phenomenon of sodium source loss, and the content of sodium doping cannot be accurately controlled. The sodium in the present invention exists in the lithium-ion solid electrolyte of the oxide. The lithium-ion solid electrolyte is obtained by liquid-phase lithium-sodium ion exchange experiment with a sodium ion conductor as a precursor, and the sodium content can be accurately controlled by the ion exchange amount. In the subsequent preparation process of the composite with the lithium-ion positive electrode material, only physical mixing and heat treatment steps are involved, and there is no sodium source loss. Therefore, the present invention has developed a new, simple, effective and controllable sodium ion doping method.

[0025] (4) The composite positive electrode material provided by the present invention is applied to lithium-ion batteries to achieve excellent capacity performance, rate performance and cycle performance. At the same time, the preparation process is green and efficient, the preparation process is simple, the application range is wide, and it can be mass-produced industrially. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions disclosed in the present invention, the following briefly introduces the drawings required for describing some embodiments disclosed in the present invention. Obviously, the drawings described below are only drawings of some embodiments disclosed in the present invention. For those skilled in the art, other drawings can also be obtained based on these drawings. In the drawings:

[0027] Figure 1 This is a SEM-Mapping image of the oxide lithium ion solid electrolyte prepared in Example 1 of the present invention;

[0028] Figure 2 This is a SEM image of the lithium-ion battery composite positive electrode material prepared in Example 1 of the present invention;

[0029] Figure 3 This is the XRD image of the lithium-ion battery composite positive electrode material prepared in Example 1 of the present invention;

[0030] Figure 4The first week charge and discharge curves of lithium ion batteries prepared using the composite positive electrode material of Example 1 and the uncoated positive electrode material respectively;

[0031] Figure 5 The figure is a rate performance curve diagram of lithium ion batteries respectively prepared by using the composite positive electrode material of Example 1 and the uncoated positive electrode material;

[0032] Figure 6 The graphs are cycle performance curves of lithium-ion batteries made using the composite positive electrode material of Example 1 and the uncoated positive electrode material. DETAILED DESCRIPTION

[0033] The technical solutions of the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the examples of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0034] The present invention provides a composite positive electrode material for a lithium ion battery, comprising a positive electrode active material, wherein the composite positive electrode material also comprises an oxide lithium ion solid electrolyte material, wherein the oxide lithium ion solid electrolyte material contains a small amount of sodium ions, and the surface of the positive electrode active material is coated with the oxide lithium ion solid electrolyte material, and the interior is doped with sodium ions.

[0035] The preparation method of the composite positive electrode material comprises the steps of:

[0036] S1. Accurately weigh the positive electrode active material and the oxide lithium ion solid electrolyte material in proportion;

[0037] S2, mixing the materials weighed in S1 and ball milling them to obtain a mixed material;

[0038] S3, placing the mixed material described in S2 in a tubular furnace, introducing oxygen, and calcining at 600-1000° C. for 8-12 hours to obtain the high-capacity lithium-ion battery composite positive electrode material.

[0039] The metal oxide crystals of Na generated on the surface of the composite positive electrode material are obtained by lithium-sodium ion exchange of sodium ions in the oxide lithium ion solid electrolyte material on the surface of the positive electrode active material.

[0040] The oxide lithium ion solid electrolyte material is obtained by liquid phase lithium sodium ion exchange experiment using sodium ion conductor as precursor, and the preparation method comprises the following steps:

[0041] A1. Mix the sodium ion conductor, lithium bis(trifluoromethylsulfonyl imide) and ionic liquid evenly, and put them into a reactor, wherein the concentration of lithium bis(trifluoromethylsulfonyl imide in the ionic liquid is 0.1 mol / L-0.5 mol / L, and the molar ratio of the lithium bis(trifluoromethylsulfonyl imide) to the sodium ion conductor is 3:1; put the reactor into a homogeneous reactor, rotate and stir at a speed of 50 rpm / min for 72-144 hours, and the temperature is 100-200°C;

[0042] A2. The product in the reactor is taken out and centrifuged, dried, and calcined at 400-500° C. to obtain an oxide lithium ion solid electrolyte material.

[0043] Preferably, the ionic liquid in step A1 is any one or more of imidazole ionic liquid, quaternary ammonium ionic liquid and pyrrole ionic liquid.

[0044] Preferably, the ionic liquid in step A1 comprises 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.

[0045] Preferably, the average particle size of the positive electrode active material is 5 μm≤D50≤20 μm, and the average particle size of the oxide lithium ion solid electrolyte material is 50 nm≤D50≤500 nm.

[0046] Preferably, the oxide lithium ion solid electrolyte material accounts for 0.5 wt.% to 3 wt.% of the composite positive electrode material.

[0047] Preferably, the positive electrode active material is any one of lithium cobalt oxide, olivine type, lithium nickel cobalt manganese oxide, lithium-rich manganese-based oxide, and spinel oxide.

[0048] Preferably, the oxide solid electrolyte material is Li 3-x Na x Zr2Si2PO 12 , Li 3-x Na x V2(PO4)3、Li 3- x Na x La(PO4)2、Li 3-x Na x Hf2Si2PO 12 , Li 4-y Na y Zr2(SiO4)3、Li 1-z Na z Zr2(PO4)3、Li 1.3-m Na m M 0.3 Ti 1.7 (PO4)3 or Li 1.3-m Nam Al 0.3 Ge 1.7 (PO4)3, wherein M is Al, Cr, Ga, Ge, Sc, In, Lu, Y or La, 0 <x<0.3,0<y<0.4,0<z<0.1,0<m<0.1。

[0049] Embodiment 1:

[0050] This embodiment provides a lithium-ion battery composite positive electrode material, including a positive electrode active material lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM811), the composite positive electrode material also includes an oxide lithium ion solid electrolyte material Li 2.5 Na 0.5 Zr2Si2PO 12 The surface of the positive electrode active material is coated with an oxide lithium ion solid electrolyte material and is doped with sodium ions inside.

[0051] The oxide lithium ion solid electrolyte material Li 2.5 Na 0.5 Zr2Si2PO 12 It is a sodium ion conductor Na3Zr2Si2PO 12 It is a precursor obtained by liquid phase lithium sodium ion exchange experiment. The preparation method includes the following steps:

[0052] (1) Sodium ion conductor Na3Zr2Si2PO 12 The mixture is uniformly mixed with lithium bis(trifluoromethylsulfonyl)imide and ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide salt, and placed in a reaction kettle. The concentration of lithium bis(trifluoromethylsulfonyl)imide in the ionic liquid is 0.5 mol / L, and the mixture is mixed with Na3Zr2Si2PO 12 The molar ratio is 3:1; the reactor is placed in a homogeneous reactor, and the reaction is stirred at a speed of 50 rpm / min for 68 hours at a temperature of 180°C;

[0053] (2) The product in the reactor is taken out and centrifuged, dried, and calcined at 450°C to obtain the oxide lithium ion solid electrolyte material Li 2.5 Na 0.5 Zr2Si2PO 12 .

[0054] Figure 1The SEM-Mapping image of the oxide lithium ion solid electrolyte prepared in Example 1 of the present invention shows that the prepared lithium ion oxide solid electrolyte contains a small amount of Na element. According to the atomic ratio calculation, the chemical formula of the solid electrolyte is Li 2.5 Na 0.5 Zr2Si2PO 12 .

[0055] The preparation method of the composite positive electrode material comprises the steps of:

[0056] (1) Accurately weigh the positive electrode active material lithium nickel cobalt manganese oxide (LiNi) at a mass ratio of 98:2. 0.8 Co 0.1 Mn 0.1 O2, NCM811) and oxide lithium ion solid electrolyte materials Li 2.5 Na 0.5 Zr2Si2PO 12 ;

[0057] (2) mixing the materials weighed in step (1) and ball milling them for half an hour to obtain a mixed material;

[0058] (3) placing the mixed material of step (2) in a tubular furnace, introducing oxygen, and calcining at 600° C. for 12 h to obtain a high-capacity lithium-ion battery composite positive electrode material.

[0059] Figure 2 This is a SEM image of the lithium-ion battery composite positive electrode material prepared in Example 1 of the present invention. It can be seen from the figure that Li 2.5 Na 0.5 Zr2Si2PO 12 Uniformly coated on the surface of the nickel cobalt manganese oxide lithium positive electrode material, and rod-shaped crystals grow on the surface. This is due to the Na + Ions pass through Li + and Na + The exchange of Na metal oxide crystals forms on the surface of the composite cathode material particles, and various defects are formed near the surface, releasing more free Li + It can make the positive electrode material have a higher capacity.

[0060] Figure 3 The XRD image of the lithium-ion battery composite positive electrode material prepared in Example 1 of the present invention shows that the composite material shows NCM811 and Li 2.5 Na 0.5 Zr2Si2PO 12 In addition to the characteristic diffraction peak of , a characteristic diffraction peak was observed at 13.8°, which can be attributed to the metal oxide of sodium (specifically, Na0.7 MnO 2.05 , JCPDS card no.27-0751). This directly proves that Li + / Na + Ion exchange.

[0061] Embodiment 2:

[0062] This embodiment provides a lithium-ion battery composite positive electrode material, including a positive electrode active material lithium-rich manganese-based oxide (Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2), the composite positive electrode material also includes an oxide lithium ion solid electrolyte material Li 2.3 Na 0.7 La(PO4)2, the surface of the positive electrode active material is coated with oxide lithium ion solid electrolyte material, and sodium ions are doped inside.

[0063] The oxide lithium ion solid electrolyte material Li 2.3 Na 0.7 La(PO4)2 is obtained by liquid phase lithium sodium ion exchange experiment using sodium ion conductor Na3La(PO4)2 as precursor. The preparation method includes the following steps:

[0064] (1) mixing sodium ion conductor Na3La(PO4)2, lithium bis(trifluoromethylsulfonyl imide) and ionic liquid 1-ethyl-3-methylimidazole bis(trifluoromethylsulfonyl imide) uniformly, and placing the mixture in a reaction kettle, wherein the concentration of lithium bis(trifluoromethylsulfonyl imide in the ionic liquid is 0.5 mol / L, and the molar ratio of the lithium bis(trifluoromethylsulfonyl imide to Na3La(PO4)2 is 2:1; placing the reaction kettle in a homogeneous reactor, rotating and stirring at a speed of 50 rpm / min for 32 h, and the temperature is 120°C;

[0065] (2) The product in the reactor is taken out and centrifuged, dried, and calcined at 400°C to obtain the oxide lithium ion solid electrolyte material Li 2.3 Na 0.7 La(PO4)2.

[0066] The preparation method of the composite positive electrode material comprises the steps of:

[0067] (1) Accurately weigh the positive electrode active material lithium-rich manganese-based oxide (Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2) and oxide lithium ion solid electrolyte materials Li 2.3 Na0.7 La(PO4)2;

[0068] (2) mixing the materials weighed in step (1) and ball milling them for half an hour to obtain a mixed material;

[0069] (3) placing the mixed material of step (2) in a tubular furnace, introducing oxygen, and calcining at 600° C. for 8 h to obtain a high-capacity lithium-ion battery composite positive electrode material.

[0070] Figure 4 The first week charge and discharge curves of lithium-ion batteries made using the composite positive electrode material of Example 2 and the uncoated positive electrode material respectively, the first week discharge capacity of the uncoated single positive electrode material is 302.2 mAh / g, after being coated with the solid electrolyte material, the first week discharge capacity of the composite positive electrode material is increased to 329.0 mAh / g, it can be seen that the capacity performance of the composite positive electrode material of the present invention is significantly improved.

[0071] Figure 5 The figure is a rate performance curve of lithium-ion batteries made of the composite positive electrode material of Example 1 and the uncoated positive electrode material. It can be seen from the figure that at different rates, the capacity of the composite positive electrode material coated with solid electrolyte is higher than that of the uncoated single positive electrode material. When the discharge rate is 1C, the discharge capacity of the uncoated single positive electrode material is 222.4mAh / g, and the 1C discharge capacity of the composite positive electrode material is increased to 299.1mAh / g. It can be seen that the coating of solid electrolyte improves the Li + The rapid transmission capability improves the rate performance of the positive electrode material.

[0072] Embodiment 3:

[0073] This embodiment provides a lithium-ion battery composite positive electrode material, including a positive electrode active material lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2, NCM811), the composite positive electrode material also includes an oxide lithium ion solid electrolyte material Li 1.2 Na 0.1 Al 0.3 Ti 1.7 (PO4)3, the surface of the positive electrode active material is coated with an oxide lithium ion solid electrolyte material, and the interior is doped with sodium ions.

[0074] The oxide lithium ion solid electrolyte material Li 1.2 Na 0.1 Al 0.3 Ti 1.7 (PO4)3 is a sodium ion conductor Na 1.3 Al 0.3Ti 1.7 (PO4)3 is a precursor obtained by liquid phase lithium sodium ion exchange experiment. The preparation method includes the following steps:

[0075] (1) Sodium ion conductor Na 1.3 Al 0.3 Ti 1.7 (PO4)3 is mixed evenly with lithium bis(trifluoromethylsulfonyl imide) and ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl imide) and placed in a reaction kettle. The concentration of lithium bis(trifluoromethylsulfonyl imide in the ionic liquid is 1 mol / L and the mixture is mixed with Na 1.3 Al 0.3 Ti 1.7 The molar ratio of (PO4)3 is 3:1; the reaction kettle is placed in a homogeneous reactor, and the mixture is stirred at a speed of 50 rpm / min for 72 h at a temperature of 180°C;

[0076] (2) The product in the reactor is taken out and centrifuged, dried, and calcined at 400°C to obtain the oxide lithium ion solid electrolyte material Li 1.2 Na 0.1 Al 0.3 Ti 1.7 (PO4)3.

[0077] The preparation method of the composite positive electrode material comprises the steps of:

[0078] (1) Accurately weigh the positive electrode active material lithium nickel cobalt manganese oxide (LiNi) at a mass ratio of 97:3. 0.8 Co 0.1 Mn 0.1 O2, NCM811) and oxide lithium ion solid electrolyte materials Li 1.2 Na 0.1 Al 0.3 Ti 1.7 (PO4)3;

[0079] (2) mixing the materials weighed in step (1) and ball milling them for half an hour to obtain a mixed material;

[0080] (3) placing the mixed material of step (2) in a tubular furnace, introducing oxygen, and calcining at 900° C. for 10 h to obtain a high-capacity lithium-ion battery composite positive electrode material.

[0081] Figure 6The cycle performance curves of lithium-ion batteries made of the composite positive electrode material of Example 3 and the uncoated positive electrode material at a high temperature of 55°C are shown. After coating with the solid electrolyte, the capacity retention rate of the material after 100 cycles is increased from 58.1% to 84.7%. It can be seen that coating with the solid electrolyte greatly improves the interface structure stability and electrochemical stability of lithium-ion batteries based on high-nickel materials.

[0082] In summary, the composite positive electrode material for lithium-ion batteries provided by the present invention realizes the combination of solid electrolyte coating and sodium ion doping by coating the positive electrode active material with a lithium ion oxide solid electrolyte containing a small amount of sodium, and has the synergistic effect of multi-scale modification. First, the surface lithium ion oxide solid electrolyte coating layer can prevent the electrolyte from dissolving and corroding the main material, improve the charge transfer at the interface, reduce the resistance of the positive electrode material and increase the electrochemical reaction rate. Secondly, the Na in the main body of the composite positive electrode material + Doping can enhance the stability of the bulk structure through the "pillar effect" and improve the capacity and rate performance of the cathode material. + / Na + The stacking fault defects caused by the exchange of sodium metal oxides can achieve a pinning effect to maintain the layer structure. Therefore, the composite positive electrode material provided by the present invention includes multi-scale modifications such as surface coating, bulk doping and defect regulation, which effectively inhibits the cracking and pulverization of the material during the cycle, stabilizes the lattice structure of the material, and effectively improves the discharge capacity, rate performance and cycle life of the positive electrode material. At the same time, the synthesis method is simple and controllable, which is conducive to large-scale production.

[0083] Although the contents of the present invention have been described in detail through the above-mentioned preferred embodiments, it should be recognized that the above description should not be regarded as limiting the present invention, and any technical personnel in this field can make possible changes and modifications to the technical solution of the present invention by using the above-mentioned disclosed contents without departing from the spirit and scope of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments according to the technical essence of the present invention without departing from the contents of the technical solution of the present invention shall fall within the protection scope of the technical solution of the present invention.

Claims

1. A lithium-ion battery composite positive electrode material, comprising a positive electrode active material, characterized in that: The composite positive electrode material also includes an oxide lithium ion solid electrolyte material, the oxide lithium ion solid electrolyte material contains sodium ions, the surface of the positive electrode active material is coated with the oxide lithium ion solid electrolyte material, and the interior is doped with sodium ions.

2. A method for preparing the composite positive electrode material for lithium-ion batteries according to claim 1, characterized in that: The preparation method comprises the following steps: S1. Accurately weigh the positive electrode active material and the oxide lithium ion solid electrolyte material in proportion; S2, mixing the materials weighed in S1 and ball milling them to obtain a mixed material; S3, placing the mixed material described in S2 in a tubular furnace, introducing oxygen, and calcining at 600-1000° C. for 8-12 hours to obtain the high-capacity lithium-ion battery composite positive electrode material.

3. The method for preparing a composite positive electrode material for a lithium ion battery according to claim 2, characterized in that: The metal oxide crystals of Na generated on the surface of the composite positive electrode material are obtained by lithium-sodium ion exchange of sodium ions in the oxide lithium ion solid electrolyte material on the surface of the positive electrode active material.

4. A lithium-ion battery composite positive electrode material according to claim 1, characterized in that: The oxide lithium ion solid electrolyte material is obtained by liquid phase lithium sodium ion exchange experiment using sodium ion conductor as precursor, and the preparation method comprises the following steps: A1. Mix the sodium ion conductor, lithium bis(trifluoromethylsulfonyl imide) and ionic liquid evenly, and put them into a reactor, wherein the concentration of lithium bis(trifluoromethylsulfonyl imide in the ionic liquid is 0.1 mol / L-0.5 mol / L, and the molar ratio of the lithium bis(trifluoromethylsulfonyl imide) to the sodium ion conductor is 3:1; put the reactor into a homogeneous reactor, rotate and stir at a speed of 50 rpm / min for 72-144 hours, and the temperature is 100-200°C; A2. The product in the reactor is taken out and centrifuged, dried, and calcined at 400-500° C. to obtain an oxide lithium ion solid electrolyte material.

5. The lithium-ion battery composite positive electrode material according to claim 4, characterized in that: The ionic liquid in step A1 is any one or more of imidazole ionic liquid, quaternary ammonium ionic liquid and pyrrole ionic liquid.

6. The lithium-ion battery composite positive electrode material according to claim 4 or 5, characterized in that: The ionic liquid in step A1 includes 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.

7. A lithium-ion battery composite positive electrode material according to claim 1, characterized in that: The average particle size of the positive electrode active material is 5 μm≤D50≤20 μm, and the average particle size of the oxide lithium ion solid electrolyte material is 50 nm≤D50≤500 nm.

8. A lithium-ion battery composite positive electrode material according to claim 1, characterized in that: The oxide lithium ion solid electrolyte material accounts for 0.5 wt. % to 3 wt. % of the composite positive electrode material.

9. A lithium-ion battery composite positive electrode material according to claim 1, characterized in that: The positive electrode active material is any one of lithium cobalt oxide, olivine type, lithium nickel cobalt manganese oxide, lithium-rich manganese-based oxide, and spinel oxide.

10. A lithium-ion battery composite positive electrode material according to claim 1, characterized in that: The oxide solid electrolyte material is Li 3-x Na x Zr2Si2PO 12 , Li 3-x Na x V2(PO4)3、Li 3-x Na x La(PO4)2、Li 3-x Na x Hf2Si2PO 12 , Li 4-y Na y Zr2(SiO4)3、Li 1-z Na z Zr2(PO4)3、Li 1.3-m Na m M 0.3 Ti 1.7 (PO4)3 or Li 1.3-m Na m Al 0.3 Ge 1.7 (PO4)3, wherein M is Al, Cr, Ga, Ge, Sc, In, Lu, Y or La, 0 <x<0.3,0<y<0.4,0<z<0.1,0<m<0.1。

Citation Information

Patent Citations

  • Lithium ion battery positive electrode material and preparation method thereof

    CN108448055A

  • Positive electrode composite material of lithium ion battery and all-solid-state battery containing the same

    CN109449414A

  • Lithium ion battery composite positive electrode material and preparation method thereof

    CN112310353A

  • Doped and coated dual-modified lithium / sodium layered metal oxide positive electrode material and one-step synthesis method therefor

    CN107369826A

  • Sodium ion gradient doped spinel structure positive electrode active material and preparation method thereof

    CN111029560A